A novel heterozygous HIF2AM535I mutation reinforces the role of oxygen sensing pathway disturbances in the pathogenesis of familial erythrocytosis - Maurizio Martini; Luciana Teofili; Tonia Cenci; Fiorina Giona; Lorenza Torti; Massimiliano Rea; Robin Foà; Giuseppe Leone; Luigi Maria Larocca (Haematologica, 2008)
HIF2A transcription factor plays a central role in the regulation of the hypoxia responding pathway in mammalian cells, by modulating erythropoiesis and angiogenesis. Molecular alterations of oxygen sensing pathway constituents are implicated in hereditary erythrocytosis. Here we show that 2 members of a family with idiopathic erythrocytosis exhibited a new heterozygous G to A mutation at base 1605 of the exon 12 of hypoxia-inducible factor-2A (HIF2A) gene. This mutation determines the replacement of methionine by isoleucine at the position 535, very close to the position 531, where the hydroxyl acceptor prolyne is located. In addition, we found that mRNA expression of erythropoietin receptor, vascular endothelial growth factor, transferrin receptor, adrenomedullin and N-myc downstream regulated gene 1, up-regulated by HIF2A or hypoxia, were significantly higher in patients carrying the mutation than in normal controls. These results suggest that the HIF2AM535I gene mutation could induce hereditary erythrocytosis at a young age.